Flooded Area Mapping and Its Relationship to the Land Use, Soil Type, and Rainfall in North Konawe Regency - Cahyono, Bowo Eko; Putri, Ervina Ikke Septiyas; Nugroho, Agung Tjahjo (Jurnal ILMU DASAR, 2022)
The flood incident in North Konawe Regency, Southeast Sulawesi that occurred on June 2nd, 2019 was the largest flood disaster in that area since the last 42 years, so it is interesting to study. As part of disaster risk management, it is necessary to do flood mapping to determine the distribution of flooded areas and identify areas that have potential for flooding. Mapping of flood inundation areas was carried out using Sentinel-1 data. Land use, rainfall and soil types are used as an analysis of their were relationship to the distribution of flood. The distribution of flood based on the identification of the presence of inundation covered 3 sub-districts, namely Oheo District, Asera District and Andowia District. Correlation of flood distribution to the land use, rainfall and soil type was identified using Pearson correlation value (r). The correlation between flood distribution and land use was -0.59 that indicates the correlation is moderate. Moreover, the correlation of flood distribution to the rainfall was 0 which means the correlation was very weak, and lastly, the correlation value of the flood distribution with soil type was 0.88 or the correlation was very strong.